2005
DOI: 10.1038/sj.onc.1209003
|View full text |Cite
|
Sign up to set email alerts
|

The ErbB-4 s80 intracellular domain is a constitutively active tyrosine kinase

Abstract: The ErbB-4 receptor tyrosine kinase homo-and heterodimerizes following heregulin binding, which provokes increased levels of tyrosine autophosphorylation. Unique to the ErbB family, ErbB-4 is then proteolytically cleaved by a-and c-secretase to produce an 80 kDa intracellular domain (s80 ICD) fragment. This fragment is found in both the cytoplasm and nucleus of many normal and cancer cells and can interact with transcription factors in the cytoplasm and nucleus. Since the s80 ICD lacks ectodomain sequences kno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
44
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(51 citation statements)
references
References 31 publications
7
44
0
Order By: Relevance
“…The resulting 'kinase-dead' ICD2 K751R mutant did not demonstrate autophosphorylation when analysed by antiphosphotyrosine Western blotting (Figure 4b), consistent with a recent report of a similar ICD2 construct (Linggi et al, 2006). Nuclear translocation of ICD2 K751R was also impaired as analysed by confocal microscopy ( Figure 4c) and quantitation of microscopy data for statistical analysis (Figure 4d).…”
Section: Erbb4 Icds Differ In Subcellular Localizationsupporting
confidence: 73%
“…The resulting 'kinase-dead' ICD2 K751R mutant did not demonstrate autophosphorylation when analysed by antiphosphotyrosine Western blotting (Figure 4b), consistent with a recent report of a similar ICD2 construct (Linggi et al, 2006). Nuclear translocation of ICD2 K751R was also impaired as analysed by confocal microscopy ( Figure 4c) and quantitation of microscopy data for statistical analysis (Figure 4d).…”
Section: Erbb4 Icds Differ In Subcellular Localizationsupporting
confidence: 73%
“…This showed increased tyrosine phosphorylation of a major 180-kDa band, the expected size of ErbB4, and a less prominent 80-kDa band in TC32 and TC71 spheroids versus monolayers. Activated ErbB4 can be proteolytically cleaved to generate a soluble 80-kDa cytosolic fragment, ErbB4-s80, which retains tyrosine kinase activity (36)(37)(38), and we hypothesized that the 80-kDa band represents ErbB4-s80. Western blots of input lysates using total ErbB4 antibodies showed similar expression of the 180-kDa ErbB4 protein in spheroids versus monolayers, whereas the 80-kDa band was not readily apparent (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In the experiments of Sheng et al (47), FGF-2 was shown to activate the rDNA promoter in a way similar to our demonstration that IRS-1 activates it. Linggi et al (48) found a nuclear fragment of ErbB-4 with an active tyrosine kinase activity. The finding that IRS-1 binds to UBF1 and stimulates rRNA synthesis (13,14) is in itself a strong suggestion of IRS-1 acting as a transcriptional cofactor.…”
Section: Discussionmentioning
confidence: 99%